USG Analysis of Learning Skills in Students with Special Needs - Hajati, Kartika; Hijayati, Siti Sofiyah; Barambangi, Jamil; Aswad, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to determine priority issues related to skills learning issues and the implications of guidance and counseling in improving online marketing skills for students with special needs. This research is descriptive research with quantitative approaches. Collecting data using interviews, observation, and documentation. Primary data sources in this study were two teachers and three students, while secondary data were documentation and pretest and posttest results. Descriptive data analysis using USG (Urgency, Seriousness, Growth). This research concludes that the analysis using USG and the analysis of determining the cause of the issue, the impact, and the parties, it can be concluded that the Core Issue, the main issue that needs to be solved immediately, namely teachers who teach skills subjects at SLBN Pasangkayu have not taught and trained students regarding marketing capabilities, including online marketing or digital marketing accompanied by the implications of the counseling services. The training program has given the expected result, which was improving the positive use of communication technology using Android-based mobile phones and the skill to market the product online. The positive impact of the Guidance and Counseling services provided can be seen in the improvement of readiness in learning, attention, and willingness to convey the learning difficulties they experience. This indicated the strengthening of students' independence.